AN ANALYSIS OF INTRALINGUAL ERRORS IN RESEARCH PROPOSALS MADE BY ENGLISH LANGUAGE AND LITERATURE STUDENTS (A STUDY WAS CONDUCTED AT UNIVERSITAS NEGERI MANADO) - Sumakul, Fransiskus Henry Daniel; Tuerah, Ignatius J.; Damopolii, Veronika L. F. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This research has the purpose of investigating intralingual errors in English Language and Literature students’ research proposals. This research is in the form of qualitative which designate the result in the form of words. The data comes from English Language and Literature students’ research proposals that were presented in research proposal seminars along the year of 2021. In administering this research, error analysis technique was implemented in order to discover the intralingual errors. The result of the study explains that the students made a total of 192 intralingual errors which are classified into 27 errors in overgeneralization, 20 errors in ignorance of rules restriction, 82 errors in incomplete application of rules and 63 errors in false concept hypothesized. It can be concluded that the intralingual errors occurred because the students did not fully understand the rules of English grammar.